Raspberry Pi and Arduino Based Autonomous Car - UJWAL L; Dr Nandini K S (IJRDO - Journal of Electrical And Electronics Engineering, 2020)
In, the recent development and trend most of the organizations are now utilizing Artificial intelligence to do autonomous tasks. Self-driving cars are one of the milestones of AI (Artificial intelligence). The mentioned method is used to reduce the human interference and takes decisions based on the surrounding environment, objects/obstacles present with the help of Convolutional neural network. These vehicular systems are now being deployed in Highways and extensively tested with worst case conditions. The system proposed here will be utilising two microcontrollers such as Raspberry Pi and Arduino, where Raspberry Pi acts as the master device which performs all the Image processing and neural networks tasks, Arduino acts as the slave device which takes the commands from the Raspberry pi, it’s purpose is to control the dc motors and help in the movement of the entire system. This system is designed in such a way that it takes autonomous decisions based on the detection of animals crossing the road, traffic light, stop sign.